Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00792-016-0878-y
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic strict anaerobic microbiota from Deschampsia antarctica vascular plants rhizosphere reveals high ecology and biotechnology relevance

Abstract: The Antarctic soil microbial community has a crucial role in the growth and stabilization of higher organisms, such as vascular plants. Analysis of the soil microbiota composition in that extreme environmental condition is crucial to understand the ecological importance and biotechnological potential. We evaluated the efficiency of isolation and abundance of strict anaerobes in the vascular plant Deschampsia antarctica rhizosphere collected in the Antarctic's Admiralty Bay and associated biodiversity to metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In addition, the sequencing of genome from culturable bacteria isolated from D. antarctica phyllosphere, showed genes associated with nutrient uptake, bioactive metabolites, and antimicrobial compounds (Cid et al, 2018). Similar to our study, Pseudomonas are commonly found in the rhizospheres and phyllospheres of Antarctic vascular plants (Teixeira et al, 2010;Peixoto et al, 2016;Cid et al, 2017). Pseudomonas is recognized as a metabolically versatile bacterial group that exhibits a wide battery of activities such as nutrient cycling, degradation of organic compounds, among others (Timmis, 2002;Loeschcke and Thies, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the sequencing of genome from culturable bacteria isolated from D. antarctica phyllosphere, showed genes associated with nutrient uptake, bioactive metabolites, and antimicrobial compounds (Cid et al, 2018). Similar to our study, Pseudomonas are commonly found in the rhizospheres and phyllospheres of Antarctic vascular plants (Teixeira et al, 2010;Peixoto et al, 2016;Cid et al, 2017). Pseudomonas is recognized as a metabolically versatile bacterial group that exhibits a wide battery of activities such as nutrient cycling, degradation of organic compounds, among others (Timmis, 2002;Loeschcke and Thies, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Microbial indicator analyses allowed identification of taxa mainly clustered into the phyla Proteobacteria, Actinobacteria, and Firmicutes, independent of niche and plant species. Members of Proteobacteria, Actinobacteria, and Firmicutes phyla are frequently reported as the dominant bacterial taxa in soil and plant microbiome in Arctic and Antarctic environments (Teixeira et al, 2010;Jorquera et al, 2016;Peixoto et al, 2016;Poosakkannu et al, 2017;Molina-Montenegro et al, 2018). In relation to three niche co-occurrence networks, our results showed significant difference among the plant niches investigated, where 5 (Microbacteriaceae, Pseudomonaceae, Lactobacillaceae, and Corynebacteriaceae), 23 (Chitinophagaceae and Sphingomonadaceae), and 7 (Rhodospirillaceae) major putative keystone taxa at family-level were observed in endosphere, phyllosphere and rhizosphere, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the bacterial genus Clostridium was found to include some endemic isolates of the Antarctic environments (Peixoto et al . 2016 ).…”
Section: Plant-associated Microbial Communities In Antarcticamentioning
confidence: 99%
“…Heterotrophy, fermentation, xenobiotic degradation, nitrogen metabolism, tryptophan metabolism and inositol metabolism were the major functional groups of plant-associated microbial communities in Antarctic regions (Peixoto et al . 2016 ; Zhang et al . 2020 ), indicating a possible adaptation strategy to harsh environmental conditions.…”
Section: Adaptation Strategies Of Plant-associated Microbial Communities To Harsh Conditionsmentioning
confidence: 99%
See 1 more Smart Citation